2002
DOI: 10.1055/s-2002-22325
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Evaluation of Activity in Inflammatory Bowel Disease by Power Doppler Sonography*

Abstract: Thickened and hypervascularized bowel wall are characteristic findings in inflammatory bowel disease. A combination of B-mode and power Doppler sonography offers an additional noninvasive procedure for the determination of activity in patients with inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
10

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 6 publications
5
28
0
10
Order By: Relevance
“…Therefore, CEUS also provides an inadequate representation of disease activity, particularly in quiescent forms of Crohn's disease (as reflected by its low specificity). Similar findings were presented by Heyne and coworkers [10]. They found that the presence of flow detected with color Doppler was correlated with disease activity in patients with ulcerative colitis, but no such correlation was observed in those with Crohn's disease.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, CEUS also provides an inadequate representation of disease activity, particularly in quiescent forms of Crohn's disease (as reflected by its low specificity). Similar findings were presented by Heyne and coworkers [10]. They found that the presence of flow detected with color Doppler was correlated with disease activity in patients with ulcerative colitis, but no such correlation was observed in those with Crohn's disease.…”
Section: Discussionsupporting
confidence: 87%
“…This disease is associated with intestinal neovascularization, as demonstrated by pathological findings [6] and by the presence of high serum levels of angiogenic factors [7]. The use of color [8] and power Doppler [9] techniques has revealed increased blood flow in the intestinal wall of patients with active disease, and the correlation between disease activity and intestinal wall vascularity has been confirmed by pulsed Doppler findings [8,10,11]. In previous studies [12e16], changes in disease activity were demonstrated by Doppler analysis of blood flow through the superior mesenteric artery.…”
Section: Introductionmentioning
confidence: 99%
“…So wurde eine Kombination von B-Mode und der Power-Dopplersonographie zur Beurteilung der Entzündungsaktivität vorgeschlagen [Heyne et al 2002]. Der Hintergrund für diesen Vorschlag war der Erfolg der neuen Ultraschallmethoden in der Detektion von langsamen Blutflüssen in kleinen Gefäßen bei anderen Körperregionen [Wermke et al 1998, Rickes et al 2000.…”
Section: Dopplershifts Sowie Ausgeprägter Inter-und Intraindividuelleunclassified
“…Erst durch die Einführung neuer Dopplerverfahren wie der Powerdopplersonographie , Newman et al 1994, Martinoli et al 1998], die es vermögen, langsame Blutflüsse in sehr kleinen Gefäßen zu detektieren, stieg wieder die Hoffnung, den Ultraschall für die Bestimmung der Aktivität einzelner Darmabschnitte zu nutzen [Heyne et al 2002]. [Graham und Jackson 1993, Munoz et al 1997, Chmura et al 2002, Kundel et al 2003, Sim et al 2005.…”
unclassified
“…But to which degree this inflammation has already evolved cannot be deduced from such an image. To accomplish this, a semiquantiative method (Heyne et al, 2002;Rogoveanu et al, 2003;Ruess et al, 2000;Spalinger et al, 2000), contrast enhanced sonographic perfusion evaluation (Girlich et al, 2009;Ripolles et al, 2009) or even better, since not requiring invasive and costly procedures, DTPM is necessary. An example of its results is shown in fib.…”
Section: Crohn Disease (Crd)mentioning
confidence: 99%